1995
DOI: 10.1007/bf01857662
|View full text |Cite
|
Sign up to set email alerts
|

The physical and psychosocial predictors of Adolescents' recovery from oral surgery

Abstract: The purpose of this study was to expand medical models of recovery from surgery in adolescents. Sixty-seven adolescents undergoing third molar surgery and their parents participated. Adolescents' negative affectivity, expectancies about recovery, coping styles, and parents' anticipated encouragement of illness behavior were assessed preoperatively. Extent of surgery was assessed by the oral surgeon. Outcome measures included mouth opening, disability, and pain. Extent of surgery did not predict recovery. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 23 publications
1
33
0
1
Order By: Relevance
“…Hansson's study 17 had the advantage of a standardised surgical procedure but, in recording on an hourly basis, may have incorporated too many measures. Gidron's study 19 failed to control for analgesic consumption.…”
Section: Dental Pain Without Psychological Manipulationmentioning
confidence: 99%
See 3 more Smart Citations
“…Hansson's study 17 had the advantage of a standardised surgical procedure but, in recording on an hourly basis, may have incorporated too many measures. Gidron's study 19 failed to control for analgesic consumption.…”
Section: Dental Pain Without Psychological Manipulationmentioning
confidence: 99%
“…The results showed that women and younger patients reported more pain, and subjects of European descent reported less pain than those of Black American and Latino descent. Gidron et al 19 examined the physical and psychosocial predictors of adolescents' recovery from oral surgery. Sixty-seven adolescents undergoing surgical removal of third molars participated in the study and the results showed that psychological factors did not predict pain.…”
Section: Dental Pain Without Psychological Manipulationmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] Similarly, the pediatric literature shows that increased attention from parents is associated with higher levels of pain complaints and disability in children with chronic pain [4][5][6][7] and delayed recovery by children undergoing painful oral surgery. 8 This research is grounded in social learning theory 9 and the findings have been interpreted as evidence that significant others may reinforce patients' pain behavior.Most research in this area uses self-report questionnaires to assess a significant other's typical behavior toward a patient with chronic pain. For example, a subscale of the Multidimensional Pain Inventory asks respondents to rate, on a scale ranging from "never" to "very frequently," how often the patient's spouse engages in solicitous behavior such as taking on the patient's chores.…”
mentioning
confidence: 99%